Ambulatory assessment as a means of longitudinal phenotypes characterization in psychiatric disorders. (January 2016) - Wenzel, Mario; Kubiak, Thomas; Ebner-Priemer, Ulrich W.
Highlights: Ambulatory Assessment is favorable for investigating gene–environment interactions. Studies on genetic influences using Ambulatory Assessment are reviewed. We describe longitudinal studies that used within-subject regulatory processes. Abstract: Ambulatory Assessment (AA) comprises the use of in-field methods to assess individuals' behavior, physiology, and the experience as they unfold in naturalistic settings. We propose that AA is favorable for the investigation of gene–environment interactions and for the search for endophenotypes, being able to assess the experienced environment and to track basic regulatory processes, such as stress reactivity, affective instability, and reward experience, which are potential common factors that underlie psychiatric disorders. In this article, we (a) first describe briefly the rationale of AA and summarize the key advantages of the approach, (b) highlight within-subject regulatory processes, such as stress reactivity, affective instability, and reward experience, (c) describe studies that used AA to examine genetic influences in psychiatric disorders, and (d) briefly review longitudinal studies that have investigated phenotypes of psychiatric disorders. The reported studies yielded promising, although sometimes inconclusive evidence for genetic effects on endophenotypes of psychiatric disorders. Moreover, most studies were twin or family studies, especially in stress-sensitivity research; thus, it is unclear which specific single nucleotide polymorphisms contribute to the endophenotypes of psychiatric disorders. We do hope that within-subject regulatory processes will enable us to clarify the fundamental psychological dimensions that cut across traditional disorders and link them to their genetic underpinnings.